Sectoral base and role of banking credit on growth: Evidence from Indonesia - Maria Magdalena Golec; Mochamad Rofik (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2023)
This study investigates the nexus of bank credit and economic growth in Indonesia, reveals the sectoral base by individual intercept, and asses too much financing through the financial deepening ratio. Exploring data from 14 sectoral economics in the 2011-2020 annual period and tackling the research objectives by applying panel regression of the fix effect model, the result shows that bank credit drives economic growth; six sectors had positive intercepted, and the rest were negative. Meanwhile, the financial deepening coefficient indicates too much financing phenomenon; therefore, elective bank credit needs to escalate